PENGEMBANGAN INSTRUMEN TES UNTUK KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS PADA MATERI ALJABAR - Kurniawati, Eka Fitri; Yuhana, Yuyu (LPPM Universitas Bina Bangsa, 2024)
This research aims to produce a test instrument for students' mathematical reflective thinking ability on algebraic material. This research used the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects used were 35 seventh grade students in one of the private junior high schools in Tangerang City. Based on the results of the material expert validation received an average score of 87.7% with very valid criteria. The validity of the items received an average of 0.82 very valid criteria. Then it has a Chronbach's Alpha value of 0.945 which means reliable. In addition, the level of difficulty of moderate questions is 3 questions, difficult 1 question and easy 1 question. The results of the student response questionnaire after working on the test instrument obtained a score of 78% with good criteria. Then based on these results, the development of test instruments for students' mathematical reflective thinking skills is valid, reliable and worthy of use